Correlates of Word Problem Solving Capabilities in Algebra of the First Year Engineering Students - Lugo, Melanie D. (JPAIR Multidisciplinary Research, 2011)
Word problems are topics in Algebra which are abhorred by most students. The study aimed at identifying the correlation that contribute to problem solving capabilities of freshmen college students who were enrolled in Algebra of De La Salle Lipa. It was anchored on three groups of correlates that contributed to problem solving capabilities of students; personal, cognitive, and social factors. The respondents' entrance examination result in Math; word problem solving scores were considered in the findings of the study. Results showed that respondents' attitude towards problem solving had affected their capabilities to a large extent. Study strategies have been affected to a large extent, while only one affected their capabilities to a small extent. There is a significant relationship between the problem solving capabilities of the students in the three factors. The common problems exhibited were wrong representation, wrong computation, and use of trial and error method, misinterpretation, forgotten formulas, and forgotten concepts. The cognitive and the social factors had a significant effect on the problem solving capabilities of the students.
Keywords: correlation; algebra; word problem solving; personal factor; cognitive factors; social factors